PERAN PUSTAKAWAN DAN KONSELOR DALAM BIBLIOTERAPI UNTUK MENINGKATKAN KESEHATAN MENTAL - Dayang Norsheila Abang Mohtar; Angeline Bisa; Wan Abdul Rahman Wan Bujang; Levas Mejus (Pustakaloka, 2025)
This paper examines how bibliotherapy can support the mental well-being of the University of Malaysia Sarawak (UNIMAS) community. During our time at UNIMAS, we observed the positive relationships and collaborations between the university librarians and UNIMAS counsellors and this made us appreciate the supportive services and teams available at the university. In addition to examining its supportive function, this paper also considers the various roles that bibliotherapy can play within the university context.The paper examines how bibliotherapeutic resources are selected and evaluated from the collection of Perpustakaan Tun Abdul Rahman Ya’kub (PeTARY) and how these resources, grounded in established bibliotherapy principles, can support the mental health of the university community and the emerging role of librarians in the profession. In this paper, we attempt to identify bibliotherapy resources that have the potential to produce positive beneficial outcomes for the UNIMAS community, construct a set of conceptual criteria for bibliotherapeutic texts selection, and investigate the correlation between library collections, user interaction, user participation, and the extent to which these selections have a meaningful impact. This paper also examines the influence of bibliotherapy on collection development and user engagement and identifies its potential of bibliotherapy to promote the professional development of librarians. The paper further evaluates how AI-enabled tools may enhance library services and improve user satisfaction. This paper demonstrates the impact of bibliotherapy on mental well-being to promote a resilient community and demonstrates the benefits of mixedmethods research.